2021
DOI: 10.3390/coatings11070758
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of High-Friction Surface Texture with Respect to Friction and Wear

Abstract: High Friction Surfaces (HFS) are applied to increase friction capacity on critical roadway sections, such as horizontal curves. HFS friction deterioration on these sections is a safety concern. This study deals with characterization of the aggregate loss, one of the main failure mechanisms of HFS, using texture parameters to study its relationship with friction. Tests are conducted on selected HFS spots with different aggregate loss severity levels at the National Center for Asphalt Technology (NCAT) Test Trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The authors have performed studies at the NCAT test track to study the characteristics of HFST aggregate loss and its relationship with friction. The authors (a) identified HFST aggregate loss characteristics (based on appearance and surface texture), including the color contrast between HFST surfaces and their background pavement colors and changes in 3D macrotexture (3), (b) characterized HFST aggregate loss using quantitative parameters, such as aggregate loss areas derived from color contrast and 3D surface macrotexture parameters derived from topographical properties (such as aggregate height, shape, and density [11]), and (c) revealed a strong correlation between DFT friction and aggregate loss areas, and, also, a strong correlation between friction (DFT60) and 3D macrotexture parameters. The authors' study provides sufficient evidence to conclude that HFST friction deterioration is largely controlled by HFST aggregate loss and change in macrotexture.…”
Section: Module 3: Hfst Performance Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have performed studies at the NCAT test track to study the characteristics of HFST aggregate loss and its relationship with friction. The authors (a) identified HFST aggregate loss characteristics (based on appearance and surface texture), including the color contrast between HFST surfaces and their background pavement colors and changes in 3D macrotexture (3), (b) characterized HFST aggregate loss using quantitative parameters, such as aggregate loss areas derived from color contrast and 3D surface macrotexture parameters derived from topographical properties (such as aggregate height, shape, and density [11]), and (c) revealed a strong correlation between DFT friction and aggregate loss areas, and, also, a strong correlation between friction (DFT60) and 3D macrotexture parameters. The authors' study provides sufficient evidence to conclude that HFST friction deterioration is largely controlled by HFST aggregate loss and change in macrotexture.…”
Section: Module 3: Hfst Performance Measuresmentioning
confidence: 99%
“…The subjectivity challenge can be addressed using 3D pavement-scanning technologies that can be used objectively to assess aggregate loss and other distresses based on texture characteristics. The observed relationship between highlighted texture parameters and DFT friction shows that texture parameters (including traditional mean profile depth, ridge to valley depth, and HFST topography-based parameters, such as average height, angularity, and density) are promising for detecting poor (low) HFST friction performance and can potentially predict low friction concerns on HFST sites (3,11). Thus, state transportation agencies can leverage their 3D pavement-scanning technologies (that state DOTs have already used to collect 3D pavement data) to cost-effectively and regularly monitor HFST friction deterioration.…”
Section: Module 4: Performance Measurement Technologies and Proceduresmentioning
confidence: 99%
“…In the domain of microstructured surfaces, tools such as confocal microscopes are often used to measure the three-dimensional topography of textured parts. However, the characterization of these surfaces often relies on a limited selection of expensive and proprietary software packages, most prominently, the software MountainsMap [16][17][18][19][20]. As such, these packages may not be available to all researchers or may be restricted to a single device license per institution, which can severely impact accessibility and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the general model that is internationally accepted to represent skid resistance performance over time or traffic, which includes three distinct phases (1,(5)(6)(7)(8)(9)(10). In the initial phase of a new pavement surface, the skid resistance increases as the binder film covering the aggregate is removed.…”
Section: Introductionmentioning
confidence: 99%